Hybridization Histochemistry of Neural Transcripts. Issue 1 (22nd January 2018) - Young, W. Scott; Song, June; Mezey, Éva
Abstract: This unit presents protocols to locate RNA transcripts in tissues. Numerous approaches are detailed, including those that use radiolabeled or colorimetric probes. Also, the probes may be modified oligodeoxynucleotides, singly or in pairs, as well as ribonucleic acids. High sensitivity and specificity are obtained, especially with sets of oligodeoxynucleotide pairs. © 2018 by John Wiley & Sons, Inc.